b - Rudolph, Thomas E.; Leonard, Vincent A. (Milwaukee, WI : Hal Leonard Books, an imprint of Hal Leonard Corporation, 2014)
"Thousands of music apps--designed to assist you with every aspect of your life as a musician, hobbyist, student, or educator--are available for the iPad. This book guides you step by step through the most popular and productive apps for the iPad 2, third- and fourth-generation iPads, iPad Air, and iPad mini. This book provides guidance for using the best iPad music apps and demonstrates how to apply them in your musical life. The authors--experienced in the creation of music technology textbooks, training, and courses--maintain a companion website that includes useful video tutorials and updates. With Musical iPad: Performing, Creating, and Learning Music on Your iPad you'll learn how to use musicianship apps to help you stay in tune and keep your voice or instrument in shape; use cloud storage to share music and data files with other devices; turn the iPad into a tuner, metronome, and practice aid; ; emulate a host of acoustic and electronic instruments; use your iPad as a virtual sheet music resource for all your performance and practice needs; learn to play an instrument with your iPad; compose and share music on your iPad; and much, much more!"--Page [4] of cover.
Getting started -- Music listening and basic tools -- Live performance -- Reading music, chords, and lyrics -- Recording -- Composing and songwriting with notation -- Learning music -- Music education -- Music and more.
Includes bibliographical references and index.
The DVD-ROM provides audio and video demonstrations of key Quick pro topics.
Keywords: iPad (Computer); Computer sound processing; Computer music -- Instruction and study